EVALUASI PERATURAN DAERAH KOTA PEKANBARU NOMOR 08 TAHUN 2014 TENTANG PENGELOLAAN SAMPAH TAHUN 2023-2024 - Wahyudi, Firma; Marta, Auradian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
ABSTRACT Waste management has become a crucial environmental issue. Pekanbaru City records the highest waste generation in Riau Province, reaching 1,011.01 tons per day. This increase is driven by population growth and the low level of public awareness and participation. The Pekanbaru City Government has responded by issuing Regional Regulation No. 08 of 2014 on Waste Management. This study aims to evaluate the implementation of the waste management policy, covering the stages of collection, transportation, processing, and final disposal. The findings indicate that policy implementation remains suboptimal due to limited budgets, inadequate infrastructure, and low community participation, highlighting the need for policy evaluation. It is concluded that waste management in Pekanbaru still faces structural and technical barriers; therefore, policy review, enforcement of sanctions, and enhanced cross-sector collaboration are required to achieve effective and sustainable waste management. Keywords: waste management, public policy, evaluation